Mixed cryoglobulinemia decelerates hepatocellular carcinoma development in hepatitis C patients with SVR by downregulating regulatory B cells: a 12-year prospective cohort study - Ming-Ling Chang; Jur-Shan Cheng; Wei-Ting Chen; Yi-Jyun Shen; Chia-Jung Kuo; Rong-Nan Chien (OncoImmunology)
How mixed cryoglobulinemia (MC) affects cancer risk in chronic hepatitis C patients with sustained virologic response (SVR) remains unclear. In a 12-year prospective study, post-SVR MC was assessed every 3‒6 months. Among the 891 SVR patients, 265 (29.7%) had baseline (24 weeks after completing anti-HCV therapy) MC, and the 12-year cancer cumulative incidence was 19.7%. Among the 73 patients who developed cancer, 37 (50.7%) had hepatocellular carcinoma (HCC), with the following associated baseline variables: for cancer, male sex, age and alanine aminotransferase (ALT) levels; for HCC, male sex, age, and cirrhosis; and for non-HCC cancer, rheumatoid factor levels. Among patients with post-SVR HCC, the mean time to HCC was longer in those with than in those without baseline MC (1545.4 ± 276.5 vs. 856.9 ± 115.2 days, p = 0.014). Patients with baseline MC had decreased circulating interleukin-10 (IL-10)-positive B cell (CD19+IL-10+cells/CD19+cells) (31.24 ± 16.14 vs. 40.08 ± 15.42%, p = 0.031), regulatory B cell (Breg) (CD19+CD24hi CD27+cells/CD19+cells) (10.45 ± 7.10 vs. 15.76 ± 9.14%, p = 0.035), IL-10-positive Breg (CD19+CD24hiCD27+IL-10+cells/CD19+cells) (5.06 ± 4.68 vs. 8.83 ± 5.46%, p = 0.015) and HCC-infiltrating Breg (18.6 ± 10 vs. 33.51 ± 6.8%, p = 0.022) ratios but comparable circulating and HCC-infiltrating regulatory T cell ratios relative to patients without baseline MC. In conclusion, old male SVR patients with elevated ALT levels or cirrhosis require intensive monitoring for cancer development, especially HCC. Tailored HCC follow-up is needed for SVR patients according to their baseline MC, which might downregulate Bregs to decelerate HCC development for almost 2 years.